Impact of Water Stress on Growth of Two Fuelwood Plants of Saudi Arabia - Al-Khalifah, N S; Khan, P R; Al Abdulkader, A M; Nasroun, T; Al-farhan, A H (Annals of Arid Zone, 2016)
This investigation reports impact of water stress on growth of Calligonlll11 C0l110SUI11and Haloxylon persicul11. both of which are a good source of fuel wood. Haloxylon experienced a significantly higher degree of water delieit than Calligonlll11. At the irrigated site Calligonul11 had significantly higher water content in relation to its dry matter content of green assimilating shoots than Haloxylon. The water deficit influenced all growth parameters. The green photosynthetic shoots were thicker and morE compressed in unirrigated samples than those taken from irrigated sites. thus resulting in the accumulation of significantly higher dry matter per unit area of green shoots in both the species. Haloxylon, being a C4 plant. exhibited vigorous growth. Irrigated lfaloxylon produced more wood than irrigated Calligonul11 when compared to their counterparts growing on the unirrigated sites. The growth of Haloxylon was enhanced due to its significantly higher chlorophyll content coupled with the water supply at the irrigated site. Haloxylon was more water saving as well as drought tolerant.